Flavivirus control of lipid metabolism: implications for virion formation, function and pathogenesis - Gullberg, Rebekah, author; Perera, Rushika, advisor; Crick, Dean, committee member; Di Pietro, Santiago, committee member; Geiss, Brian, committee member; Wilusz, Jeff, committee member (Colorado State University. Libraries, 2018)
Dengue viruses (DENV) are the most aggressive arthropod-born viruses worldwide with no currently available antivirals. There is a clear need to understand host viral interactions that can be exploited for therapeutic options. DENV are members of the Flaviviridae family with a positive sense single-stranded RNA genome surrounded by a virally encoded capsid protein, a host cell derived lipid envelope and an icosahedral shell of virally encoded glycoproteins. Its genome is replicated in virally–induced invaginations in the endoplasmic reticulum of the host cell that consistently develop in a time-dependent manner. These invaginations display a highly curved architecture and seem to increase the membrane contact sites within the ER and its vicinity. Functionally, these membranes condense the replication machinery, provide a scaffold to coordinate replication, and hide the viral double stranded RNA intermediate from the host cellular defenses. It has been shown that fatty acid synthesis is increased during infection to provide substrates for this membrane expansion. To identify further changes to cellular metabolism, we have profiled the metabolome of DENV serotype 2 (DENV2) infected Human Hepatoma cells (Huh7) cells at key time-points in virus replication. We have found time-dependent changes in cellular essential fatty acid metabolism. Furthermore, we have interrogated a library of siRNAs directed at the unsaturated fatty acid biosynthesis pathway to determine key enzymes involved in viral replication. We have identified that stearoyl Co-A desaturase 1 (SCD1), the rate-limiting enzyme responsible for converting stearic to oleic acid, is critical for viral replication, maturation and infectious particle formation. Finally, we have profiled the serum metabolome of acute-phase patients with dengue diseases, chikungunya virus infection, or an unknown febrile illness to identify metabolic changes with potential use as prognostic biomarkers. Hypothesis: Since dengue viruses are enveloped viruses, lipid metabolites in the human host are a critical resource hijacked by these viruses for their replicative advantage. Important metabolites will be altered during infection in a time dependent manner and can be quantified and correlated directly to their role in viral genome replication and infectious particle assembly and release. These metabolic changes could also be identified in human bio-fluids and could function as early biomarkers of disease manifestation.